Use of the World Wide Web in research: randomization in a multicenter clinical trial of treatment for twin-twin transfusion syndrome. - Dorman, K; Saade, G R; Smith, H; Moise, K J Jr (Obstetrics & Gynecology, 2000)
Objective: To describe the process involved in using the World Wide Web to coordinate a randomized, multicenter international trial of treatment for twin-twin transfusion syndrome.Method: A Web site was designed by members of the research team, a Web consultant, and a senior computer programmer. The original intent was to provide patient randomization only, but the Web site later was designed so that centers could download a data collection form. Data could be entered directly into the Web site and subsequently imported into a database at the coordinating center.Experience: The Web site has been active for 3 years, with 13 participating centers and 31 patients enrolled.Comment: Use of the World Wide Web to coordinate an international, multicenter trial is an efficient method. Although there are many benefits, the most obvious is the capability to initiate and conduct a large international trial at minimal cost.